Ceramide Synthase 5 Is Essential to Maintain C(16:0)-Ceramide Pools and Contributes to the Development of Diet-induced Obesity - Gosejacob, Dominic (J Biol Chem, 2016)
Ceramides are bioactive sphingolipids, which are composed of sphingoid bases carrying acyl chains of various lengths. Ceramides are synthesized by a family of six ceramide synthases (CerS) in mammals, which produce ceramides with different N-linked acyl chains. Increased ceramide levels are known to contribute to the development of obesity and insulin resistance. Recently, it has been demonstrated that the ceramide acylation pattern is of particular importance for an organism to maintain energy homeostasis. However, which of the CerS family members are involved in this process is not yet completely known. Using newly developed CerS5 knock-out mice, we show here that CerS5 is essential to maintain cellular C(16:0) sphingolipid pools in lung, spleen, muscle, liver, and white adipose tissue. Glycerophospholipid levels in CerS5-deficient mice were not altered. We found a strong impact of CerS5-dependent ceramide synthesis in white adipose tissue after high fat diet feeding. In skeletal muscle, liver, and spleen, C(16:0)-ceramide levels were altered independent of feeding conditions. The loss of CerS5 is associated with reduced weight gain and improved systemic health, including maintenance of glucose homeostasis and reduced white adipose tissue inflammation after high fat diet challenge. Our findings indicate that reduction of endogenous C(16:0)-ceramide by genetic inhibition of CerS5 is sufficient to ameliorate obesity and its comorbidities.